(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2018)
The Phoridae species recorded in Uruguay are presented based on the bibliographical review of the Family and the study of specimens deposited in the collection of the University of Cambridge, England. The presence of seven species of Phoridae in Uruguay is confirmed: Dohrniphora cornuta (Bigot, 1857), Megaselia imitatrix Borgmeier, 1969, Megaselia rufipes (Meigen 1804), Megaselia scalaris (Loew, 1866), Syneura cocciphila (Coquillet, 1895), Puliciphora borinquensis Wheeler, 1906 y Puliciphora rufipes Silva Figueroa, 1916. The last two species are recorded for the first time for the country.